The Benefits of Solar Home Systems : An Analysis from Bangladesh - Samad, Hussain A.; Khandker, Shahidur R.; Asaduzzaman, M.; Yunus, Mohammad (World Bank, Washington, DC, 2014)
The Government of Bangladesh, with help from the World Bank and other donors, has provided aid to a local agency called Infrastructure Development Company Limited and its partner organizations to devise a credit scheme for marketing solar home system units and making these an affordable alternative to grid electricity for poor people in remote areas. This paper uses household survey data to examine the financing scheme behind the dissemination of these solar home systems, in particular the role of the subsidy; the factors that determine the adoption of the systems in rural Bangladesh; and the welfare impacts of such adoption. The paper finds that while the subsidy has been declining over time, the demand for solar home systems has seen phenomenal growth, mostly because of technological developments that have made the systems increasingly more affordable. Households with better physical and educational endowments are more likely to adopt solar home systems than poor households. The price of the system matters in household decision making -- a 10 percent decline in the price of the system increases the overall demand for a solar panel by 2 percent. As for the benefits, adoption of a solar home system improves children s evening study time, lowers kerosene consumption, and provides health benefits for household members, in particular for women. It is also found to increase women's decision-making ability in certain household affairs. Finally, it is found to increase household consumption expenditure, although at a small scale.